The Launch of Studies in Learning and Teaching (SiLeT) - Nadi Suprapto; Binar Kurnia Prahani; Mohd Nor Syahrir Abdullah; Tsung-Hui Cheng (Studies in Learning and Teaching, 2020)
This short paper introduces ‘Studies in Learning and Teaching’ (SiLeT) as a new journal. As an international peer-reviewed journal, SiLeT aware of the quality of the content. The rational, the purpose, and the scope are illustrated as the opening speech of the journal. Since the number of learning and teaching journals is still lacking in accommodating the ideas of researchers and scholars in the world especially in the domain of education, therefore, the existence of SiLeT will fill the void of scientific discussion, especially in terms of “learning, teaching, curriculum development, learning environments, teacher education, educational technology, educational developments, measurement and evaluation, educational statistics, books review of education and other learning-teaching issues”.